PENDIDIKAN ANTI KORUPSI DAN PENGARUHNYA TERHADAP INTEGRITAS MAHASISWA - Junaidin Basri; Husnan Sulaiman; Irma Indriyani (Almarhalah | Jurnal Pendidikan Islam, 2022)
AbstractThis study aims to determine whether there is an influence between Anti-Corruption Education on Student Integrity. The method used in this research is quantitative with a descriptive analysis approach. After being analyzed using statistics, it can be concluded that there is an effect of the implementation of anti-corruption education on the integrity of students by 13.69% while the remaining 86.31% is the influence of other factors. Significance test with 0.05 confidence obtained that 4.18 from  . Based on the results of the analysis, it shows that there is a correlation between the implementation of anti-corruption education and the integrity of students. Keyword: Anti-Corruption, Education and Student Integrity